Enhancement of protective vaccine-induced antibody titer to swine diseases and growth performance by Amino-Zn, yucca extract, and β-mannanase feed additive in wean-finishing pigs - Sampath, Vetriselvi; Cho, Sungbo; Lee, Byung Ryol; Kim, Nam-Hun; Kim, In Ho (Frontiers in Veterinary Science, 2023)
The primary purpose of this research is to determine the effect of Zinc-oxide (ZnO), yucca schidigera extract (YE), and β-mannanase enzyme supplementation on growth performance, nutrient digestibility, fecal gas emission, and immune response in pigs. A total of 180 crossbred pigs (6.57± 1 kg) were randomly assigned to one of three dietary treatments: CON-corn soybean meal (basal diet); TRT1-CON+ 1000 ppm ZnO +0.07% Yucca extract (YE) + 0.05% β-mannanase; and TRT2-CON+ 2000 ppm ZnO + 0.07% YE+ 0.05% β-mannanase for 22 weeks. Each treatment had 12 replicates with 5 pigs per pen. Pigs fed diet supplement with ZnO, YE, and β-mannanase linearly increased (P<0.05) BW and average daily gain at weeks 6,12,17, and 18. In contrast, the gain-to-feed ratio showed a linear increase (P<0.05) from weeks 6 to 17 and the overall trial period. Moreover, the inclusion of experimental diets linearly decreased (P > 0.05) noxious gas emissions such as ammonia, hydrogen sulfide, Acetic acid, carbon dioxide, and Methyl mercaptans. The dietary inclusion of ZnO, YE, and β-mannanase significantly increased the serological immune responses to Mycoplasma hyopneumoniae (MH) and Foot and mouth disease virus (FMDV-O Type) at the end of week 6 and porcine circovirus-2 (PCV-2) at week 19. Based on the result, we infer that the combination of ZnO, YE, and β-mannanase supplement would serve as a novel in-feed additive to enhance the growth performance and act as a boosting agent and immune stimulatory to increase the efficacy of swine vaccinations.